О выборе структуры модели комбинированной системы отопления - Левченко, С. А.; Баташова, Н. А.; Мных, А. С. (НТУ "ХПИ", 2010)
The resulted recommendations about relation to the basic elements of heating combined system model structure and the structure is offered in the article for combining different energy sources. The use of external temperatures generator is also offered for dynamic of the model.
Keywords: отопление; энергетическое оборудование; теплоизоляционные материалы; комбинированная система отопления; тепловая мощность; теплообменник